2017
DOI: 10.4067/s0718-221x2017005000401
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Cistus ladanifer and Erica arborea shrubs for fuel: Wood and bark thermal characterization

Abstract: As a form of upgraded biomass characterized by its high energy density, low production costs, and low process energy requirements, wood pellets are an environmentally friendly fuel allowing for carbon neutral heating with high energy efficiency. In this work, the suitability of a valorization of the woods from the two most representative shrub species from the Iberian Peninsula (namely Cistus ladanifer and Erica arborea) for heating has been assessed. Whereas Erica arborea met the requirements of ISO 17225-2:2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
(6 reference statements)
0
7
1
1
Order By: Relevance
“…Among the shrub species, it was verified that these were the ones that presented lower values and, within this group, the outstanding species is the Erica arborea, with contents very close to 25%. Compared with other similar works, namely Carriou-Prieto [64], Tsounamis [65] and Leroy et al [66], it was found that the content obtained is overestimated. However, it is judged that the significant difference of contents is due to the difference in extraction method.…”
Section: Extractivescontrasting
confidence: 66%
“…Among the shrub species, it was verified that these were the ones that presented lower values and, within this group, the outstanding species is the Erica arborea, with contents very close to 25%. Compared with other similar works, namely Carriou-Prieto [64], Tsounamis [65] and Leroy et al [66], it was found that the content obtained is overestimated. However, it is judged that the significant difference of contents is due to the difference in extraction method.…”
Section: Extractivescontrasting
confidence: 66%
“…The calculated higher heating values (HHV) for green stems, brown stems and twigs were 19.67, 20.4 and 20.63 kJ·g −1 , respectively, with a mean value of 20.2 kJ·g −1 . For comparison purposes, the HHV values for other Mediterranean shrubs, i.e., C. ladanifer and E. arborea , ranged from 19.2 to 20.5 kJ·g −1 and from 19.7 to 21.3 kJ·g −1 , respectively [ 14 ]. Regarding the applicability of the above shrubs as fuels, the European standard for wood pellets (EN 14961-2) establishes that the HHV should be ≥18.82 kJ·g −1 [ 15 ], so E. horridum aerial samples would be compliant.…”
Section: Resultsmentioning
confidence: 99%
“…Main exothermic effects in the DSC curves of E. horridum fractions associated with holocellulose and lignin combustion. Those of C. ladanifer and E. arborea are included for comparison purposes[14]. T peak stands for exotherm peak temperature.…”
mentioning
confidence: 99%
“…The chosen area (> 1,2 ha) is a mixed shrubland in which the dominant shrub species are Cistus ladanifer L. and Erica arborea L. (Carrión-Prieto et al 2017a). Details on the sampling procedure, stem diameters, chemical composition and vegetal components can be found in Carrión-Prieto et al (2017b).…”
Section: Methodsmentioning
confidence: 99%